2019
DOI: 10.1016/j.jclepro.2018.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of virtual water flows on regional water scarcity in China

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 71 publications
1
60
0
Order By: Relevance
“…By comparing the results for the years, 2007 and 2010, we found that eight provinces (i.e., Jiangxi, Shandong, Zhejiang, Shanghai, Beijing, Ningxia, Guangdong, and Hainan) had a decreased WF. The largest decrease was witnessed in Jiangxi, which was 1.72 billion m 3 The results revealed that, on average, the proportions of external WF for the years, 2007 and 2010, were 40.20% and 41.11%, respectively ( Figure 2). In 2010, Tianjin, Shanghai, and Beijing featured the largest proportions of external WF, which were 88.54%, 88.43%, and 79.44%, respectively, indicating that these regions relied heavily on VW imports.…”
Section: Data Sourcesmentioning
confidence: 95%
See 2 more Smart Citations
“…By comparing the results for the years, 2007 and 2010, we found that eight provinces (i.e., Jiangxi, Shandong, Zhejiang, Shanghai, Beijing, Ningxia, Guangdong, and Hainan) had a decreased WF. The largest decrease was witnessed in Jiangxi, which was 1.72 billion m 3 The results revealed that, on average, the proportions of external WF for the years, 2007 and 2010, were 40.20% and 41.11%, respectively ( Figure 2). In 2010, Tianjin, Shanghai, and Beijing featured the largest proportions of external WF, which were 88.54%, 88.43%, and 79.44%, respectively, indicating that these regions relied heavily on VW imports.…”
Section: Data Sourcesmentioning
confidence: 95%
“…Most of the VSW came from northern provinces (Figure 6a, b). For instance, Xinjiang (66.14 billion m 3…”
Section: Inter-regional Virtual Scarce Water Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the economic development consumed a lot of water. The "Western Development" strategy has enabled the central and western provinces to obtain economic benefits [17], but it has exacerbated local water consumption and caused severe water pollution. Finally, the agricultural irrigation consumed a lot of water [3].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the virtual water strategy provides a new way to alleviate the pressure of regional water shortage. Based on the perspective of consumption, it transfers water-intensive products through trading to solve the problem of unbalanced distribution of regional water resources [17].…”
Section: Introductionmentioning
confidence: 99%